FEATURES OF PRELIMINARY AND PERIODIC MEDICAL EXAMINATIONS OF SHIFT PERSONNEL IN THE ARCTIC SHELF - N. I. Dubinina; G. N. Degteva; Y. A. Korneyeva (Acta Biomedica Scientifica, 2012)
The article discusses the problems of grounding for additional documentation in the preliminary examination of a candidate to shift work in the Arctic shelf, of choosing the variant of preliminary and. periodic medical examinations in order to increase the effectiveness of medical support during the manufacturing process of medical screening, improving the effectiveness of periodic inspection, when combining it with the dispensary inspection.